A comprehensive survey on the occurrence of Polerovirus (Solemoviridae) causing yellowing disease on cucurbitaceous crops in Tamil Nadu, India - Bharath, B S; Nagendran, K; Boopathi, N; Sivagnanapzham, K; Harish, S; Shanmugam, P S; Praneetha, S; Gandhi, Karthikeyan (Journal of Horticultural Sciences, 2025)
A roving survey was conducted in and around Coimbatore, Dindigul, and Tiruchirappalli districts of Tamil Nadu, where commercially field-grown bitter gourd, ridge gourd, pumpkin, sponge gourd, snake gourd, and bottle gourd were observed to exhibit virus symptoms such as yellowing with interveinal chlorosis, downward rolling, and mottling of leaves along with stunted plant growth. Sampling of symptomatic leaves from infected fields revealed an average yellowing disease incidence of 54.42% among the different cucurbitaceous crops. Molecular assay through reverse transcription-PCR (RT-PCR) using universal and specific primer pairs of Polerovirus performed with the collected symptomatic leaf samples confirmed the association of Polerovirus. In addition, samples tested through dot immune binding assay (DIBA) using polyclonal antibody of Cucurbit aphid-borne yellows virus (CABYV) also tested positive. The results revealed that 81% and 100% of symptomatic samples were detected with Poleroviruses through RT-PCR and DIBA assays, respectively. The amplified DNA fragments of the RNA-dependent RNA polymerase (RdRp) gene and coat protein (CP) gene of Polerovirus associated with bitter gourd were cloned using the pGEM-T vector and sequenced in both orientations. Nucleotide sequencing analysis of the RdRp and CP genes confirmed the association of Cucurbit aphid-borne yellows virus (CABYV), a Polerovirus belonging to the family Solemoviridae, sharing an identity of 96.34% and 100%, respectively. Phylogenetic analysis of the RdRp genomic region of CABYV showed clustering with various isolates from the Asian continent, whereas the CP genomic region exhibited minimal variation within the amplified region, grouping into a single cluster with isolates from Asia, North America, Europe, and South America. These results confirm the alarming occurrence of Polerovirus causing yellowing disease in cucurbitaceous crops in Tamil Nadu.